Isolated Horner’s Syndrome Secondary To Rhinosinusitis: A Case Report And Literature Review - Jamir Pitton Rissardo; Ana Letícia Fornari Caprara; Juliana Oliveira Freitas Silveira; Paulo Gilberto Medeiros Jauris (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery, 2020)
Abstract Background Horner’s syndrome (HS) is characterized by unilateral ptosis, ipsilateral miosis with normally reactive pupil, and in some cases, ipsilateral facial anhidrosis. Case presentation We report an adult male presenting with ptosis. Neurological examination revealed ptosis and miosis in the right eye. Anhidrosis was not observed, and the patient did not complain about it. Laboratory tests were within normal limits. He had searched a general practitioner because of purulent nasal discharge, nasal obstruction, and anosmia. He was diagnosed with acute rhinosinusitis. Symptomatic treatment was started. The subject had full recovery of the nasal symptoms, but his right upper eyelid was drooping progressively. In the follow-up, after the third month, the patient was recovering from ptosis and miosis. In 1 year, the ptosis was minor with less than 1 mm and miosis was no more observed. Discussion A few cases of HS secondary to a sinus infection have been reported in the literature. To the authors’ knowledge, there are only two case reports of individuals who developed sinusitis and Horner’s syndrome. The present case is the first to present isolated HS features. Our report suggests that sinusitis should be listed as a probable cause of isolated Horner’s syndrome. Moreover, patients presenting with this presentation probably have a good prognosis.